User image construction framework based on big data fusion background for power grid business travel - Changhao ZHANG; Zhiyong YU; Zhen ZHOU; Ruijie SHI; Xinyong WANG (Dianxin kexue)
Business travel planning decisions based on big data analysis are an important part of controlling travel dynamics and developing travel specifications.Based on the information of the national network business travel information,aiming at the optimization of the travel mode during the travel process and the personal preference of hotel accommodation,a user portrait framework technology was constructed to realize the rapid and accurate identification of sensitive customer groups.Firstly,the user's sensitivity was predicted by two-channel modeling for different characteristics of users.Secondly,users were characterized by business approval,travel control,hotel evaluation,time characteristics,numerical characteristics,etc.,and users’ multi-source feature system was constructed.Finally,business travel data was fully utilized.Multi-source,create a multi-view fusion model based on double-layer XGBoost,improve classification accuracy,and verify the effectiveness of the method by comparing experiments.